2002
DOI: 10.1016/s0022-0248(01)01757-2
|View full text |Cite
|
Sign up to set email alerts
|

Composition and lattice structure of fivefold twinned nanorods of silver

Abstract: Multiply twinned silver particles of rod-like shape and nanometer dimensions prepared by inert-gas aggregation technique have been studied by high-resolution electron microscopy. These pentagonal nanorods exhibit aspect ratio between 1.8 and 6 with the length of their fivefold axis ranging from 22 to 132 nm. Digital image processing and evaluation was utilised to characterise composition and lattice structure of the nanorods. Measuring the spacings of lattice plane fringes of nanorod subunits in various orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
49
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 31 publications
12
49
1
Order By: Relevance
“…11 The analytical model includes the energy of the dipyramidal structure at both ends of the nanowire because the majority of experimental studies show growth along two dipyramidal ends. 7,9,12,20 The ends are also considered for the nontwinned nanorod, which was assumed to be a truncated octahedron, consistent with the Wulff construction. The end structures for the nontwinned nanorod are shown in Fig.…”
Section: Analytical Model For the Nanorods Including The Endsmentioning
confidence: 99%
See 2 more Smart Citations
“…11 The analytical model includes the energy of the dipyramidal structure at both ends of the nanowire because the majority of experimental studies show growth along two dipyramidal ends. 7,9,12,20 The ends are also considered for the nontwinned nanorod, which was assumed to be a truncated octahedron, consistent with the Wulff construction. The end structures for the nontwinned nanorod are shown in Fig.…”
Section: Analytical Model For the Nanorods Including The Endsmentioning
confidence: 99%
“…[4][5][6] The current study focuses on silver ͑Ag͒ nanowires, which have great potential for higher strengths due to the existence of multiple twinned structures. [7][8][9][10][11] The increased strength in the multitwinned nanorods has been attributed to the twinned structure's ability to hinder dislocation motion and generate work hardening in the material. 1,12 Multitwinned particulates are used as seeds to grow multitwinned nanorods ͑MTRs͒ and have been observed for over half a century starting with their discovery by Ino in 1966.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that silver one-dimensional (1D) nanostructure consists of arranged subunits around a fivefold axis instead of a single crystal. [17] The uniaxial growth of silver nanowires was illustrated based on Ag:O coordination of the absorbed polyvinylpyrrolidone (PVP) on Ag nanowires' surfaces. [18] Furthermore, the growth mechanisms of Ag nanostructures via microwave-polyol method in the presence of Pt as the catalyst have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The important role of twinning in determining the habit of the final morphology will also be discussed. One interesting feature of silver, gold, and copper pentagonal cross-section nanowires, is their remarkable structure (Gao et al, 2003;Giersig et al, 2004;Hofmeister et al, 2002;Sun et al, 2002;Zhao et al, 2005). It has been proposed that this structure evolved from a multi-twin decahedral nanoparticle growing in the [110] direction by stabilizing more effectively the newly formed 100 facets than the 111 facets and their electron diffraction patterns present "forbidden" spots.…”
Section: Introductionmentioning
confidence: 99%